Identification and Data Processing Methods in Metabolomics. - Rudaz, Serge (Future Science Group, 2014)
Developments in computational analysis have furthered metabolomics research greatly. This book highlights the data processing and analysis techniques, systems, strategies and software used in metabolomics, with a particular focus on novel or advanced applications.